Biofilm formation of multidrug-resistant Staphylococcus aureus on stainless steel surfaces and the effect of disinfectants in eliminating biofilm - Jamaludin, Nur Syifa' (2019)
Staphylococcus aureus is a pathogenic bacterium capable of adhering and forming a biofilm on food processing surfaces, thus causing the cross-contamination of foods. The adhered biofilm can detach from the surface and easily contaminate food as it passes through the surface and leaves toxins. In Malaysia, multidrug-resistant Staphylococcus aureus (MDRSA) has been studied in the context of the foodservice environment but the findings on the survival of MDRSA in forming biofilm on stainless steel surfaces and the resistance towards commercial disinfectant are limited. The objectives of this study were 1) to isolate and characterize S. aureus from food contact surfaces for the antibiotic-resistant properties, 2) to study the adherence and biofilm formation of the MDRSA on stainless steel surfaces at 25oC and 37oC, and 3) to examine the effect of disinfectants in eliminating the biofilm produced by MDRSA on stainless steel surface at 37oC. A total of 38 S. aureus isolated from food contact surface by biochemical test were tested for the antibiotic resistance by using five classes of antibiotics; Penicillin (I), Cephalosporins (II), Amino-glycosides (III), Quinolones Fluoroquinolone (IV), and Sulphonamide (V) by the standard procedures of Kirby-Bauer disc diffusion method. The adherence and biofilm assay performed using 23 MDRSA cultures placed on stainless steel discs at 25°C and 37°C for (24, 48, and 72) hours in adherence and (3, 6, 9, 12, and 15) days in biofilm. The elimination of biofilm was completed on three MDRSA cultures at 37oC on 9 days using three concentrations of peracetic acid and sodium hypochlorite; 0.01%, 0.02%, and 0.03%. As a result, all the MDRSA can adhere on stainless steel with a minimum 4.00 log CFU/mL. The adherence of MDRSA on stainless steel during 24, 48 and 72 hours ranged from 4.11 to 6.55 log CFU/mL and 4.25 to 6.86 log CFU/ml at 25oC and 37oC, respectively. The highest adherence was found on 48 hours at both temperatures. The biofilm formation of MDRSA on 3, 6, 9, 12, and 15 days ranged from 3.56 to 6.80 log CFU/mL and 3.74 to 7.05 log CFU/mL at 25oC and 37oC, respectively. SA18 exhibited the best biofilm formation on Day 9 at both temperatures because of the highest viable cell (log CFU/ml) that formed on the stainless steel surfaces. The MDRSA cultures revealed a high capacity to adhere and form biofilm on stainless steel at 37oC. As for the disinfectants, sodium hypochlorite was found to be more effective than peracetic acid at eliminating the biofilm, with a log reduction ranging from 2.48–3.54 log CFU/mL in all concentrations. In conclusion, the MDRSA cultures can strongly adhere and form biofilm on stainless steel at their optimum growth temperature. Nevertheless, the biofilm can be eliminated using sodium hypochlorite, which could be a sufficient disinfectant for reducing biofilm formation in the food industry.